2016
DOI: 10.3747/pdi.2014.00284
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis Fluid and Some of its Components Potentiate Fibrocyte Differentiation

Abstract: Long-term peritoneal dialysis (PD) often results in the development of peritoneal fibrosis. In many other fibrosing diseases, monocytes enter the fibrotic lesion and differentiate into fibro-blast-like cells called fibrocytes. We find that peritoneal tissue from short-term PD patients contains few fibrocytes, while fibrocytes are readily observed in the peritoneal membrane of long-term PD patients. The PD fluid Dianeal (Baxter Healthcare Corporation, Deerfield, IL, USA) contains dextrose, a number of electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In our view, the fact of a decrease in ferroxidase activity of CP in PD patients and its correlation with the dialysis adequacy is explained by PD solutions' uses which contain dextrose as an osmolyte, lactate as a buffer, and different electrolytes, including chloride. [31]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our view, the fact of a decrease in ferroxidase activity of CP in PD patients and its correlation with the dialysis adequacy is explained by PD solutions' uses which contain dextrose as an osmolyte, lactate as a buffer, and different electrolytes, including chloride. [31]…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fact that most patients included in the present study (89%) received commercial glucose-containing PD fluids, the low-serum CP level might be mediated by the following mechanisms: (1) an increase in oxidative status due to the accumulation in the peritoneum of GDP with formation of free radicals, and[32] (2) the presence of chloride in the abdominal cavity (96 mmol/l in each 1000 ml of dianeal PD solution)[31] whereas its presence is not found in other pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One compound that may be clinically relevant is NaCl, which when added to increase the medium NaCl concentration by 25 mM (this level of increase can be seen in the serum after a very salty meal) potentiates fibrocyte differentiation and inhibits the SAP effect, possibly explaining why high salt intake is associated with a propensity for cardiac fibrosis ( 137 ). Peritoneal dialysis can lead to peritoneal fibrosis, and we found that peritoneal dialysis fluid and dialysis fluid components such as NaCl also promote fibrocyte differentiation and impede SAP ( 139 ). In support of this connection between salt and fibrocytes, low dietary salt reduces the severity of bleomycin-induced pulmonary fibrosis in mice, suggesting that low salt diets may be beneficial for fibrosis patients ( 143 ).…”
Section: Sap Inhibition Of Fibrocytes Allows An Assessment Of the Posmentioning
confidence: 99%